Antihypercholesterolemic and Antioxidative Potential of an Extract of the Plant, Piper betle, and Its Active Constituent, Eugenol, in Triton WR-1339-Induced Hypercholesterolemia in Experimental Rats. (9th January 2014) - Venkadeswaran, Karuppasamy; Muralidharan, Arumugam Ramachandran; Annadurai, Thangaraj; Ruban, Vasanthakumar Vasantha; Sundararajan, Mahalingam; Anandhi, Ramalingam; Thomas, Philip A.; Geraldine, Pitchairaj
Abstract : Hypercholesterolemia is a dominant risk factor for atherosclerosis and cardiovascular diseases. In the present study, the putative antihypercholesterolemic and antioxidative properties of an ethanolic extract of Piper betle and of its active constituent, eugenol, were evaluated in experimental hypercholesterolemia induced by a single intraperitoneal injection of Triton WR-1339 (300 mg/kg b.wt) in Wistar rats. Saline-treated hypercholesterolemic rats revealed significantly higher mean blood/serum levels of glucose, total cholesterol, triglycerides, low density and very low density lipoprotein cholesterol, and of serum hepatic marker enzymes; in addition, significantly lower mean serum levels of high density lipoprotein cholesterol and significantly lower mean activities of enzymatic antioxidants and nonenzymatic antioxidants were noted in hepatic tissue samples from saline-treated hypercholesterolemic rats, compared to controls. However, in hypercholesterolemic rats receiving the Piper betle extract (500 mg/kg b.wt) or eugenol (5 mg/kg b.wt) for seven days orally, all these parameters were significantly better than those in saline-treated hypercholesterolemic rats. The hypercholesterolemia-ameliorating effect was better defined in eugenol-treated than in Piper betle extract-treated rats, being as effective as that of the standard lipid-lowering drug, lovastatin (10 mg/kg b.wt). These results suggest that eugenol, an active constituent of the Piper betle extract, possesses antihypercholesterolemic and other activities in experimental hypercholesterolemic Wistar rats.